CAMBIO ORGANIZACIONAL Y POLÍTICA DE INCENTIVOS EN LAS UNIVERSIDADES PÚBLICAS: EXPERIENCIA EN EL ÁREA DE LAS CIENCIAS SOCIALES EN UNA UNIVERSIDAD MEXICANA - Chauca Malásqueza, Pablo Manuel (2019)
The work displays an interpretation of the factors that make possible the application of a system of incentives based on academic merits in the public universities. The discussion considers from the perspective of the organizational and institutional change. It is argued that the development of a system of incentives in the public institutions of superior education is associate to transformations in the level of the academic actors (individual and groups), in the institutional level (rules and forms of coordination) and in the level of the interactions with the surroundings. It is maintained that these transformations imply as well changes in the government forms, in the forms of management, the sources of financing, the relations of education - investigation, and in the criteria of validation of results. Like illustration, one comments throughout the text, about the experience in the field of social sciences in a public university of the interior of the Mexican Republic.